Synthesis of Novel Quinazolinone Derivatives with Methyl (E)-2-(3-methoxy)acrylate Moiety - Dong, Kui-kui; Zhou, Hua-hong; Guo, A-rong; Chen, Tian; Wang, Yu-liang (Asian Journal of Chemistry, 2012)
A new series of quinazolinone derivatives with methyl (E)-2-(3-methoxy)acrylate moiety have been designed and synthesized. All target compounds had been identified by 1H NMR spectrum, IR spectrum and HR-MS (high resolution mass spectrum). Three target compounds (10a, 10e, 10h) were chosen to preliminarily test the antibacterial activities, the results showed that all three target compounds exhibited antibacterial activities against three bacterial strains (Proteobacteria, Salmonella, Colibacillus).